Production of novel recycled hybrid metal matrix composites using optimized stir squeeze casting technique - Mourad, Abdel-Hamid Ismail; Christy, John Victor; Krishnan, Pradeep Kumar; Mozumder, Mohammad Sayem (Journal of manufacturing processes, 2023)
In this work, optimized squeeze stir casting was used to produce recycled Aluminum Metal Matrix Composites (AMC's). Scrap Aluminum Alloy Wheel (SAAW), sourced from the local markets was used as a matrix. Alumina (5 %), SiC (3 & 6 %) and graphite (1, 3 & 4 %) were used as hybrid reinforcements to create the sustainable MMC's. The produced recycled hybrid AMCs were subjected to mechanical tests such as porosity, tension, compression, hardness and wear analysis. The highest ultimate tensile strength of 250 MPa was recorded for AMC with 4 % graphite inclusion, followed by AMC with 3 % SiC. The highest compressive strength was noted at 508 MPa for 4 % graphite, followed by composite with 3 % graphite and 3 % SiC. Similarly highest wear resistance was exhibited by AMC with 4 % graphite and alumina. The results showed that the addition of 4 % graphite and alumina to SAAW increased the strength and decreased the wear rate and frictional forces. The microstructure analysis conducted on these samples confirmed that graphite and alumina exhibited better bonding to the SAAW matrix than SiC. Conventional Friction Stir Welding (FSW) technique was employed to check the weldability of the developed AMCs. Tensile test of the welded samples confirm that recycled AMCs with 4 % graphite are very strong and can be introduced to the industry for various applications.